2018
DOI: 10.11114/ijsss.v6i5.3234
|View full text |Cite
|
Sign up to set email alerts
|

The Role Stress Has on the Creative Process of Problem-Solving Projects: A Case Study of Individuals and Collaboration

Abstract: This study examined interior design and fashion merchandising students because they creatively solve everyday consumer problems and employers competitively screen graduates for their creative and collaborative abilities. Students in these fields not only have to fulfill course requirements, but they also must exhibit a high level of creativity and be able to work with others. To examine the influence stress may have on the creative process of problem-solving, students working alone were compared to students wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Design projects are often ill‐defined and become more complex at higher levels of study. Related research on mental health in Architecture education (although not in a distance setting) revealed that:
… students will incur stress at various times throughout the design process, the perceived levels of student stress progressively increased and shifted during the research, exploration, refinement, and finalization design phases of project solution (Gomez‐Lanier 2018, 46)
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design projects are often ill‐defined and become more complex at higher levels of study. Related research on mental health in Architecture education (although not in a distance setting) revealed that:
… students will incur stress at various times throughout the design process, the perceived levels of student stress progressively increased and shifted during the research, exploration, refinement, and finalization design phases of project solution (Gomez‐Lanier 2018, 46)
…”
Section: Introductionmentioning
confidence: 99%
“…… students will incur stress at various times throughout the design process, the perceived levels of student stress progressively increased and shifted during the research, exploration, refinement, and finalization design phases of project solution (Gomez‐Lanier 2018, 46)…”
Section: Introductionmentioning
confidence: 99%